Moderasi Beragama bagi Remaja di Desa Langgen Kecamatan Talang Kabupaten Tegal - Jannah, Miftahul; Khakim, Abdul; Maualana, Muhamad; Lathifah, Hani; Ningrum, Nur Oktavia; Yupitania, Yayi Anti (Profetik: Jurnal Pengabdian Masyarakat, 2023)
By having a strong Islamic religious style, so that to increase knowledge and attitudes about religious moderation for Muslim teenagers, an interactive and interesting activity is needed, therefore a seminar on religious moderation for teenagers is being held, this activity is part of efforts to prevent the rise of radicalism and intolerance and to find out what kind of scientific paradigm is used to deal with these problems. The existence of religious moderation can provide every individual teenager with the opportunity to determine their right to choose religious practices. During adolescence it is easy for them to make the right choice, which has a positive impact on each teenager. The research method used is a qualitative approach.